2009
DOI: 10.1177/0022057409189001-205
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Gap: Addressing the Vocabulary Needs of English-Language Learners in Bilingual and Mainstream Classrooms

Abstract: Gaps in reading performance between Anglo and Latino children are associated with gaps in vocabulary knowledge. An intervention was designed to enhance fifth graders' academic vocabulary. The meanings of academically useful words were taught together with strategies for using information from context, from morphology, from knowledge about multiple meanings, and from cognates to infer word meaning. Among the principles underlying the intervention were that new words should be encountered in meaningful text, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
251
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(265 citation statements)
references
References 17 publications
8
251
2
4
Order By: Relevance
“…A similarly structured intervention, the Vocabulary Improvement Program (Carlo et al, 2004), obtained an effect size of .50. The Stahl and Fairbanks (1986) metaanalysis of vocabulary curricula reviewed studies with effect sizes ranging as high as 2 under short-term laboratory-teaching conditions and as low as 0 under more authentic educational conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A similarly structured intervention, the Vocabulary Improvement Program (Carlo et al, 2004), obtained an effect size of .50. The Stahl and Fairbanks (1986) metaanalysis of vocabulary curricula reviewed studies with effect sizes ranging as high as 2 under short-term laboratory-teaching conditions and as low as 0 under more authentic educational conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Estos programas generalmente presentan una combinación de aprendizaje incidental y de instrucción directa que incorpora a la enseñanza de palabras individuales, la enseñanza de estrategias de aprendizaje léxico para la inferencia del significado de las palabras desconocidas, y que proporciona múltiples oportunidades para el descubrimiento de nuevas palabras en textos reales (Baumann, Edwards, Font, Tereshinski, Kame'enui y Olejnik 2002;Beck, McKeown y Omanson 1987;Carlo et al 2004). …”
Section: Enseñanza Efectiva Del Vocabulariounclassified
“…Tal y como observamos en el apartado sobre conocimiento del vocabulario, el grupo experimental mostró ganancias mayores en la comprensión de lectura que el grupo de control. Por otra parte, dado que la instrucción se centró en el desarrollo del vocabulario y no en las habilidades de comprensión lectora, el hecho de que hubiera cualquier mejora en la comprensión de lectura es ya notable y corrobora los resultados de estudios anteriores que han mostrado que la enseñanza de vocabulario tiene un impacto positivo en la capacidad de comprensión de lectora (por ejemplo, Carlo et al 2004;McKeown et al 1983;Beck et al 1987). Cuando los resultados se desagregaron adicionalmente por la lengua materna de los participantes, se encontró que las puntuaciones medias de comprensión lectora de los hablantes nativos de español eran más altas que las de los hablantes nativos de inglés, tanto para el grupo experimental como el de control (véase la Tabla 6).…”
Section: Comprensión De Lecturaunclassified
“…These tools draw on research in education, which found that text adaptation can improve the reading comprehension skills for learners of English (Yano et al, 1994;Carlo et al, 2004). The language learning technology often consists of methods for text simplification and adaptation, which is performed either at syntactic (Carroll et al, 1999;Siddharthan et al, 2004) or lexical level (Carroll et al, 1998;Devlin et al, 2000;Burstein et al, 2007).…”
Section: Introductionmentioning
confidence: 99%